2009
DOI: 10.1080/10256010903083995
|View full text |Cite
|
Sign up to set email alerts
|

L-[1-13C]phenylalanine breath test in patients with chronic liver disease of different etiologies

Abstract: The aim of this study was to compare the oxidation of L-[1-(13)C]phenylalanine ((13)C-PheOx) in patients with chronic liver failure due to different etiologies using L-[1-(13)C]phenylalanine breath test. Breath samples were collected before the administration of 100 mg L-[1-(13)C]phenylalanine, and every 10 min thereafter until completion of 1 h. Control subjects (n=9) presented a larger cumulative percentage of (13)C dose recovery (CPDR) than patients (n=124) with chronic liver disease, regardless of the etio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…The use of stable isotope based breath tests in clinical conditions are well known, with the 13 C-urea breath test for the detection of H Pylori infection in the stomach being the most well established as a routine test [29]. 1-13 C-phenylalanine oxidation to 13 CO 2 is also used as a test for chronic liver disease [30] and gastric emptying [31]. While it is likely that measurement of blood phenylalanine levels will remain the key measure of clinical management, there is a need for a routine, simple test to help better manage PKU children.…”
Section: Discussionmentioning
confidence: 99%
“…The use of stable isotope based breath tests in clinical conditions are well known, with the 13 C-urea breath test for the detection of H Pylori infection in the stomach being the most well established as a routine test [29]. 1-13 C-phenylalanine oxidation to 13 CO 2 is also used as a test for chronic liver disease [30] and gastric emptying [31]. While it is likely that measurement of blood phenylalanine levels will remain the key measure of clinical management, there is a need for a routine, simple test to help better manage PKU children.…”
Section: Discussionmentioning
confidence: 99%
“…This is a potential barrier to routine clinical employment of 13 C-labelled compound breath tests for liver function assessment. The PBT is useful for evaluating alcohol-related liver dysfunction [8]. As a Downloaded by [University of Toronto Libraries] at 21:26 25 December 2014 specific dose of phenylalanine must be administered to treat hepatic coma, this agent is acceptable even for subjects with a very poor liver function.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to 13 C breath tests for cytosol, the usefulness of the l-[1-13 C]phenylalanine breath test (PBT) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and [ 13 C]galactose breath test [26][27][28][29][30][31] has been reported. Several studies focusing on mitochondria indicated the usefulness of the α-ketoisocaproate breath test [32][33][34][35][36][37][38] and methionine breath test (MethioBT) [39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…This test, however, confirmed its usefulness by discriminating between groups of patients with compensated and decompensated cirrhosis, as well as between patients with oesophageal varices of varying degrees of severity [ 35 , 36 ]. Another study showed that the Phe-BT result was an independent survival predictor in patients with hepatic impairment [ 37 ].…”
Section: Breath Testsmentioning
confidence: 98%